IMPROVING INNOVATION PROCESS MANAGEMENT AT ENTERPRISES - Kuzmina, Evgenia; Beketova, Olga; Belousova, Irina; Dudina, Elena; Shadskaja, Irina (Revista Inclusiones, 2020)
The article deals with the development of approaches to improving the innovation process management at enterprises. It is established that the innovative development of enterprises is an integral part of the innovative development of the economy and an important aspect of the reproduction of the industrial relations, and it includes the renewal of the composition and construction of fixed assets. It is revealed that each organization that is engaged in entrepreneurial activity should have more innovative ideas and projects in stock than it can actually implement, because otherwise, the enterprise may find itself on the path leading to stagnation and bankruptcy. It is proved that in the context of a dynamically changing economy and increasing market competition, the emerging advanced technologies can determine the prospects for the enterprise’s activity. It is determined that the flexibility of the enterprise, its adaptability to innovations remains the main and only key factor of its survival and development.